2014
DOI: 10.1111/ans.12895
|View full text |Cite
|
Sign up to set email alerts
|

Internal hemipelvectomy with reconstruction for primary pelvic neoplasm: a systematic review

Abstract: This comprehensive review provided informative details regarding the goals, outcomes and complications associated with this procedure and underscored the need for further investigation into the various surgical approaches currently available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
2
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 23 publications
(56 reference statements)
1
35
2
7
Order By: Relevance
“…'s research (13) showed that 2 of the 14 patients undergoing allograft reconstruction after partial hemipelvectomy of pubis had infection and 1 had hardware failure with nonunion. In Shao's review (24), the allograft reconstruction group reported a wound infection rate ranging from 7.7 to 37.5% and an implant breakage or displacement rate that ranged from 7.7 to 12.5%. In our study, No dislocation and infection of prosthesis was found until the last follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…'s research (13) showed that 2 of the 14 patients undergoing allograft reconstruction after partial hemipelvectomy of pubis had infection and 1 had hardware failure with nonunion. In Shao's review (24), the allograft reconstruction group reported a wound infection rate ranging from 7.7 to 37.5% and an implant breakage or displacement rate that ranged from 7.7 to 12.5%. In our study, No dislocation and infection of prosthesis was found until the last follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…According to Enneking classification, the procedure can be divided into the following types: Type I, iliac bone wing; Type II, acetabular region; Type III, ischium and pubis; Type IV, total hemipelvis. In this case, Type I resection is performed by a supra-acetabular osteotomy and disarticulation of the sacroiliac joint, and Type II resection may require the removal of the femoral head and mobilization of the iliac vessels [12]. Several reports have been published describing this technique and the analysis of results for patients with bone and soft tumors of the pelvic region who underwent different modalities of internal hemipelvectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Although biologically based reconstructions such as allografts have potential advantages in patients undergoing pelvic tumor resections whose oncologic prognosis is good, autograft pelvic reconstruction after periacetabular tumor resection has rarely been reported [2,19]. Endoprosthetic replacement after tumor resection in the pelvis is associated with a high risk of complications and functional restrictions [3,15,17,26]. In 2009, we therefore began to use the ipsilateral femoral head as an autograft to support a cemented THA for acetabular reconstruction after tumor resection in a way analogous to patients undergoing THA for developmental hip dysplasia [18,27], although even during this time our preferred approach was endoprosthetic replacement.…”
Section: Discussionmentioning
confidence: 99%
“…Pelvic reconstruction after periacetabular tumor resection is technically difficult and associated with high complication rates and functional limitations. Commonly used methods include hip transposition, arthrodesis, autograft with recycled tumor-bearing bone, allograft-prosthetic composite, and custom-made or modular pelvic prostheses [26]. Pseudarthrosis and arthrodesis elicit stable long-term effects but result in problems with hip function and leg length discrepancy [24,25].…”
Section: Introductionmentioning
confidence: 99%